The Students’ Need in Writing Skills - Nehru P. Pongsapan (Jurnal Keguruan dan Ilmu Pendidikan, 2017)
Objective of this research was to find out the need of the third semester students of English Department of FKIP UKI Toraja in academic 2014/2015. Significant of this research expected to be useful information for lecturer and students in writing skills. In this research the writer used quantitative method to describe the need of the third semester students of English Department of FKIP UKI Toraja in writing skills. The population of this research was the third semester students of English Department of FKIP UKI Toraja in academic 2014/2015 consist of 132 students, because the number of population was big so the writer only took 28 students as a sample (cluster sampling). In collecting the data the writer used one part of instruments, namely: Questionnaire. Questionnaire significan to find out the students’ need in writing skills. Based on the result of analysis the data showed that the students need in writing skills are: (a)Using correct punctuation and spelling, (b)structuring sentences, (c)appropriate vocabulary, (d)the knowledge of vocabulary, (e)expressing ideas appropriately, (f)developing ideas, (g)organizing paragraph (h)the overall writing ability, (i)the creative writing, (j)the essay writing, and (k)writing introductions and conclusions.